Decentralized Systems of Health Care Delivery and the Role of Large Cities : A Comparative Analysis - di Gropello, Emanuela (World Bank, Washington, DC, 2013)
South Africa is going through an important political and administrative reorganization and a series of structural reforms. The responsibility for primary health care, which was mostly provincial, is about to be decentralized to the Local Government level. The main purpose of this paper is to analyze the on-going decentralization process in the Gauteng province and determine the role that Great Johannesburg can play within this new decentralized framework. To extract lessons and recommendations for Gauteng and Johannesburg, the paper takes a close look at the case of three middle -income Latin American countries, Chile, Colombia and Brazil, which offer valuable experience in the design and implementation of decentralized systems of health care delivery at the country and city level. It also looks at other international experiences. At the city level, the paper concludes that the case of Bogota in Colombia seems to be particularly relevant to the selection of a decentralized health care model for Johannesburg. It also shows that, in the longer run, the experiences provided by the current reforms in the UK and New Zealand would be worth looking at. Finally, a more general conclusion of the report is the finding that there is a wide range of possible roles for large cities in primary health care delivery and that the extent of this role will very much depend on the decentralization strategy adopted at the national level and on a number of key characteristics at the city level, among which the political and administrative structure, the fiscal and institutional capacity and the demographic structure could be identified.